A Coupled Ketoreductase‐Diaphorase Assay for the Detection of Polyethylene Terephthalate‐Hydrolyzing Activity. Issue 9 (19th April 2022) - Gimeno‐Pérez, María; Finnigan, James D.; Echeverria, Coro; Charnock, Simon J.; Hidalgo, Aurelio; Mate, Diana M.
Abstract: In the last two decades, several PET‐degrading enzymes from already known microorganisms or metagenomic sources have been discovered to face the growing environmental concern of polyethylene terephthalate (PET) accumulation. However, there is a limited number of high‐throughput screening protocols for PET‐hydrolyzing activity that avoid the use of surrogate substrates. Herein, a microplate fluorescence screening assay was described. It was based on the coupled activity of ketoreductases (KREDs) and diaphorase to release resorufin in the presence of the products of PET degradation. Six KREDs were identified in a commercial panel that were able to use the PET building block, ethylene glycol, as substrate. The most efficient KRED, KRED61, was combined with the diaphorase from Clostridium kluyveri to monitor the PET degradation reaction catalyzed by the thermostable variant of the cutinase‐type polyesterase from Saccharomonospora viridis AHK190. The PET degradation products were measured both fluorimetrically and by HPLC, with excellent correlation between both methods. Abstract : Degrade‐detect‐validate : A sensitive, real‐substrate, real‐time, fluorescence‐based enzymatic assay for the degradation products of polyethylene terephthalate (PET) and polyethylene furanoate (PEF) plastics was developed. It was based on the simultaneous oxidation of ethylene glycol to glyoxal by ketoreductase (KRED) and the reduction of resazurin to the highly fluorescent resorufin by diaphorase. Assay was validated against HPLC.